Priming Low-Dose Gamma Irradiation Increases Cellular Radioadaptation Response through the Induction of Hsp70 and SOD2 - S. Supriyadi (Atom Indonesia, 2021)
Exposure to low-dose radiation has been demonstrated to stimulate increased cell protection when receiving subsequent challenge dose in what is known as radioadaptation response. Hsp70 and SOD, especially SOD2, are cytoprotectors against superoxide radicals generated by radiation exposure. This study aims to measure the expressions of Hsp70 and SOD2 in parotid salivary gland acinar cells as an indicator of radioadaptation response stimulated by low-dose gamma irradiation. The study used 24 male Rattus norvegicus that are divided into four groups: normal control, positive control, with 50-mGy priming irradiation, and with 100-mGy priming irradiation. The animals were immobilized without anesthetics with special tools designed especially for this study. Irradiation was carried out using a cobalt-60 (gamma ray) teletherapy unit (Philips XK-100) directed to the dorsa of the animals’ heads. High-dose gamma irradiation (2 Gy) was administered 5 hours after priming irradiation. The expression of Hsp70 and SOD2 was measured through immunohistochemical technique on the parotid salivary gland acinar cells and observed using a light microscope with 1000× magnification. Data obtained was analyzed with one-way ANOVA test (α = 0.05). The results showed that Hsp70 and SOD2 expressions in the priming irradiation groups were higher than those in control groups. The conclusion of this study: priming irradiation with low-dose gamma radiation before challenge irradiation with high-dose gamma radiation increases the radioadaptation response of salivary gland acinar cells through induction of Hsp70 and SOD2.